The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1021/acssuschemeng.3c04125
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Edge Fe-N4 Active Sites on N-Doped Porous Carbon Nanosheets Derived from Zeolitic-Imidazolate Frameworks for High-Efficiency Oxygen Reduction

Shujun Jiang,
Guanying Ye,
Weiwei Zhu
et al.

Abstract: Defect and morphology engineering of metalnitrogen codoped carbon (M-N/C) has been proven to be efficacious in promoting the oxygen reduction reaction (ORR) catalytic activity, yet the simultaneous construction of active sites with high intrinsic activity and efficient exposure is a challenge. Herein, an Fe-N/C catalyst consisting of edge Fe-N 4 sites atomically dispersed on porous carbon nanosheets (e-Fe-N/C NS ) is designed for high intrinsic catalytic active as well as efficient utilization. By combining an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
(76 reference statements)
0
1
1
Order By: Relevance
“…The N 1s signals can be described as three types of nitrogen species, i.e., pyridinic N (398.68 eV), pyrrolic N (400.80 eV), and graphitic N (402.79 eV), , and their relative contents are listed in Table S1. Previous reports have shown that pyridinic N might serve as anchor points for Fe atoms. Remarkably, we did not detect any Fe 2p signal in the XPS spectra in both Fe 3 ACCs and Fe SACs, likely due to the low Fe loading …”
Section: Resultscontrasting
confidence: 50%
“…The N 1s signals can be described as three types of nitrogen species, i.e., pyridinic N (398.68 eV), pyrrolic N (400.80 eV), and graphitic N (402.79 eV), , and their relative contents are listed in Table S1. Previous reports have shown that pyridinic N might serve as anchor points for Fe atoms. Remarkably, we did not detect any Fe 2p signal in the XPS spectra in both Fe 3 ACCs and Fe SACs, likely due to the low Fe loading …”
Section: Resultscontrasting
confidence: 50%
“…Owing to their superior catalytic activity, structural stability, and cost-effectiveness, atomically dispersed single-atom catalysts (SACs) with nitrogen-coordinated metal sites (M-N x –C) have been considered the most promising Pt-based alternatives for the ORR among various PGM-free electrocatalysts. Both the active site density and the intrinsic activity are crucial for acquiring a high catalytic activity of SACs. Recently, significant progresses have been made in achieving high site densities and an increased intrinsic activity of M–N–C catalysts. Excessive amounts of the metal source were generally added to obtain high-density M-N x sites, which usually led to metal-atom agglomeration and nanoparticle formation during pyrolysis, thus resulting in the low utilization of active sites and an impeded mass transfer for the ORR. , In this respect, the catalyst performance for the ORR could be improved by increasing the catalyst intrinsic activity while ensuring the monoatomic dispersion of M-N x sites. The modulation of coordination environments around the M-N x sites either from the first coordination shell (coordination atoms and coordination numbers) or the peripheral shell (heteroatom doping and local carbon structure) enabled the precise tailoring of the electronic structure of SACs, which influenced their interaction with oxygen intermediates, thus performing an efficient ORR. , …”
Section: Introductionmentioning
confidence: 99%